2016
DOI: 10.1126/scitranslmed.aad5222
|View full text |Cite
|
Sign up to set email alerts
|

Early memory phenotypes drive T cell proliferation in patients with pediatric malignancies

Abstract: Engineered T cell therapies have begun to demonstrate impressive clinical responses in patients with B cell malignancies. Despite this efficacy, many patients are unable to receive T cell therapy because of failure of in vitro expansion, a necessary component of cell manufacture and a predictor of in vivo activity. To evaluate the biology underlying these functional differences, we investigated T cell expansion potential and memory phenotype during chemotherapy in pediatric patients with acute lymphoblastic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(227 citation statements)
references
References 29 publications
7
218
0
2
Order By: Relevance
“…15 Moreover, unselected populations, especially those skewed toward T EM and T TE , often fail to generate viable clinical products due to poor in vitro cell expansion. 16 Recently, several clinical trials in which tumor-redirected T cells were derived from T CM have been reported. 17,18 However, clinical exploitation of T SCM has so far been hampered by their relative paucity in the circulation and the lack of robust, clinical-grade protocols capable of isolating and maintaining this cell type in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, unselected populations, especially those skewed toward T EM and T TE , often fail to generate viable clinical products due to poor in vitro cell expansion. 16 Recently, several clinical trials in which tumor-redirected T cells were derived from T CM have been reported. 17,18 However, clinical exploitation of T SCM has so far been hampered by their relative paucity in the circulation and the lack of robust, clinical-grade protocols capable of isolating and maintaining this cell type in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our study was not biased due to exclusion of patients with poor lymphocyte numbers and function. A clinical trial of CD19 CAR-T cell therapy for pediatric B-ALL excluded 24% of patients due to the failure of T cells to meet predefined criteria for in vitro proliferation (21).…”
Section: Transgene Immune Responses Limit Persistence and Efficacy Ofmentioning
confidence: 99%
“…Yet, the expansion efficiency is likely lower with patient-derived cell material, although such difference was not observed in this study. Efficient expansion in the absence of IL-2 can also be obtained using IL-7 and IL-15, which was needed especially for patients with lymphoma [28].…”
Section: Discussionmentioning
confidence: 99%